Destination competitiveness: how does travel experience influence choice?. Issue 13 (2nd July 2020) - Neto, Ambrozio Queiroz; Dimmock, Kay; Lohmann, Gui; Scott, Noel
ABSTRACT: Traditionally, previous studies regard destination competitiveness as a static concept. More recent studies adopting a demand perspective consider competitiveness to be dynamic, with destination competitiveness varying according to tourism niche. Competitiveness also varies within tourist segments in the same niche. The authors apply the concept of travel experience to understand destination competitiveness better. Using the SCUBA diving tourism niche, the authors investigate the extent to which tourists' level of travel experience influences the importance they give to destination competitiveness attributes in a hypothetical SCUBA diving destination. Cluster analysis of results from an online survey ( n = 712) revealed three groups with different levels of travel experience. Significant differences among the three groups were apparent in seven of ten destination competitiveness factors. The findings demonstrate the dynamism of destination competitiveness when measured from the demand perspective. Results also demonstrate that travel experience is an appropriate characteristic for classifying tourists regarding destination competitiveness attributes.